Growth and development and their environmental and biological determinants - Kelly da Rocha Neves; Rosane Luzia de Souza Morais; Romero Alves Teixeira; Priscilla Avelino Ferreira Pinto (Brazilian Society of Pediatrics, 2016)
Objective: To investigate child growth, cognitive/language development, and their environmental and biological determinants. Methods: This was a cross‐sectional, predictive correlation study with all 92 children aged 24 to 36 months who attended the municipal early childhood education network in a town in the Vale do Jequitinhonha region, in 2011. The socioeconomic profile was determined using the questionnaire of the Associação Brasileira de Empresas de Pesquisa. The socio‐demographicand maternal and child health profiles were created through a self‐prepared questionnaire. The height‐for‐age indicator was selected to represent growth. Cognitive/language development was assessed through the Bayley Scale of Infant and Toddler Development. The quality of educational environments was assessed by Infant/Toddler Environment Scale; the home environment was assessed by the Home Observation for Measurement of the Environment. The neighborhood quality was determined by a self‐prepared questionnaire. A multivariate linear regression analysis was performed. Results: Families were predominantly from socioeconomic class D, with low parental education. The prevalence of stunted growth was 14.1%; cognitive and language development were below average at 28.6% and 28.3%, respectively. Educational institutions were classified as inadequate, and 69.6% of homes were classified as presenting a risk for development. Factors such as access to parks and pharmacies and perceived security received the worst score regarding neighborhood environment. Biological variables showed a greater association with growth and environmental variables with development. Conclusion: The results showed a high prevalence of stunting and below‐average results for cognitive/language development among the participating children. Both environmental and biological factors were related to growth and development. However, biological variables showed a greater association with growth, whereas environmental variables were associated with development.